Useful trees of the secondary deciduous tropical forest in Villa Allende Forest Reserve, Chiapas, Mexico - Rodríguez Larramendi, Luis Alfredo; Sánchez Cortés, María Silvia; Gordillo Ruiz, Mercedes Concepción (Instituto de Ecología, A.C., 2018)
Background and Aims: The tropical deciduous forest (TDF) stands out for its utilitarian value, although the information related to the use of plants by mestizo communities is limited. This research describes the use value and the ecological importance of native TDF secondary tree species near peasant communities in Villa Allende Forest Reserve, Chiapas, Mexico.   Methods: The ethnobotanical information was obtained via the free list technique complemented with a floristic inventory through the method of plots. The use value index was calculated as a measure of cultural importance and it was related to the ecological importance value of each useful species, using relative values of frequency, density and dominance. Key results: one hundred three useful angiosperm species were found, 77% of them are of multiple use and correspond to 10 categories in use, being the most remarkable: fuel (73), poles (68) and construction (63). Eysenhardtia adenostylis (1.36) and Acacia pennatula (1.29) were the species with the highest use value, although the majority (84%) registered low use values (≤0.3). Likewise, the species with the highest use value have low values of ecological importance (IVI ≤0.69). The use value per species was not related to the ecological importance value, except the dominance associated with the forest of 19 years of abandonment that correlated positively with the use value (rs=0.30, P=0.04) and the significant correlation between density and value of ornamental use (rs=0.41, P=0.03). Based on use value, nine potential species were recommended for conservation and restoration of TDF in the study area.Conclusions: The secondary TDF in Villa Allende Forest Reserve, Chiapas, provides useful tree species to satisfy the basic needs of the communities, although the cultural importance of these does not depend on its ecological importance.